The Rebirth of the neues museum is the latest stage in the architectural and political evolution of the spreeinsel, Berlin's historic Museum Island - Balfour, Alan
Juvet Lanscape Hotel, en Gudbrandsjuvet, Norddal, Noruega, diseñado por el estudio Jensen & Skodvin.